Intelligent analysis of radar data based on fuzzy transforms - Solonskaya, S.; Zhyrnov, V. (Radiotekhnika, 2018)
It is proposed to use a fuzzy transform apparatus for the analysis of radar data in the form of coordinates of marks and their virtual images formed on the basis of useful and interfering signals, and which are considered as fuzzy samples and sets. It is shown how this approach can be used to identify the functional (semantic) dependencies between components of the radar data.